Pengembangan sistem informasi pembangunan daerah berbasis website menggunakan metode waterfall - Tulkhoiriyah, Inayah; Dwi Kurniawan, Safar; Darmanto, Darmanto (Applied Information Technology and Computer Science (AICOMS), 2024)
Regional Development is a crucial aspect in achieving community progress and welfare. The Regional Development Information System (SIPD) serves as a vital tool in supporting the planning, management, and monitoring of development projects. This study discusses the development of a web-based SIPD using the Waterfall software development method. The Waterfall method was chosen for its structured and linear framework, with clear stages from analysis to design, implementation, testing, and maintenance. The study focuses on the design and implementation of a system capable of presenting regional development information transparently and accurately to the public. The development of SIPD involves several steps, including requirements analysis, responsive user interface design, integration of project monitoring features, and testing to ensure the system's reliability and security. Implementing the website as the primary platform enables easy access for stakeholders, including local governments, the public, and related parties. The results of this study indicate that the development of a web-based SIPD using the Waterfall method provides an efficient and structured solution. The system facilitates quick and easy access to regional development information, enhances transparency, and strengthens public involvement in the development process. Therefore, the application of the Waterfall method in the development of a web-based SIPD is expected to provide a solid foundation for improving the effectiveness of regional development planning and management.